1981
DOI: 10.1038/bjc.1981.95
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent detection of hormone receptors in cutaneous melanocytic tumours

Abstract: Summary.-Immunofluorescent assessment of hormone receptors in melanocytic tumours is quite feasible without loss of diagnostic material, in contrast to the impracticability of quantitative biochemical assays. Using this method, oestrogen receptors were demonstrated in 4/6, and progesterone receptors in 3/5 patients with metastatic melanoma. Receptors were not found in 3 patients with primary cutaneous melanomas of the superficial spreading type. Progesterone receptors were present in the junctional component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Estrogen receptors have been found on melanoma cells (Grill et al, 1982; Ellis et al, 1985a,b; Ellis and Wheeland, 1986; Thompson et al, 1981). The fact that female hormones may have a protective effect in patients with MM (Briele et al, 1983) possibly is a factor in why females have thinner lesions.…”
Section: Section VIImentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen receptors have been found on melanoma cells (Grill et al, 1982; Ellis et al, 1985a,b; Ellis and Wheeland, 1986; Thompson et al, 1981). The fact that female hormones may have a protective effect in patients with MM (Briele et al, 1983) possibly is a factor in why females have thinner lesions.…”
Section: Section VIImentioning
confidence: 99%
“… Brocker et al, 1984, 1985; Bumol and Reisfeld, 1982; Ellis et al, 1985b; Ellis and Wheeland, 1986; Halpern et al, 1985; Hearing, 1981; Herlyn et al, 1983; Hersey, 1985; Imai et al, 1981; Imam et al, 1986; Kantor et al, 1982; Knudsen et al, 1982; Kozlowski et al, 1984; Natali et al, 1983a,b, 1985; Nicolson, 1982; Real et al, 1985; Ruiter et al, 1985; Sherwin et al, 1979; Stefansson et al, 1982; Thompson et al, 1981; Tomita et al, 1985; Wakabayashi et al, 1984; Watanabe et al, 1982. …”
mentioning
confidence: 99%
“…We are currently investigating this possibility. Previous studies have shown an occasional positive “normal nevus, “ 4, 9, 14 but controls have not been well defined. One study by Chadhuri and colleagues 15 found that 41% of benign nevi from patients with melanoma were positive for estrogen receptors, stressing that control patient populations must be rigidly outlined.…”
Section: Commentsmentioning
confidence: 97%
“…This method allows visualization of the cells that bind the fluorescent hormones. One previous report used a similar assay, with negative fluorescence obtained on three primary superficial spreading melanomas 9 . We also did estrogen‐ and progesterone‐binding studies on nevi from a control male and female patient population.…”
mentioning
confidence: 99%
See 1 more Smart Citation